Analisis Manajemen Risiko Usaha Ayam Broiler Bapak M. Yusuf di Kabupaten Dharmasraya Ditinjau dari Manajemen Bisnis Syariah - Seni Syaftela.Z; Harfandi Harfandi (Lembaga Yasin AlSys, 2026)
Although research on risk management in broiler chicken businesses has developed, studies that specifically integrate risk management with the perspective of Sharia business management in smallholder poultry farming remain limited. This study aims to analyze risk management in Mr. M. Yusuf’s broiler chicken business in Dharmasraya Regency and to review its implementation from the perspective of Sharia business management. This study employed a qualitative approach with a case study design, involving five informants selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using the descriptive qualitative analysis technique of the Miles and Huberman model. The results showed that the broiler chicken business faced four main types of risk, namely production risk, price and market risk, financial risk, and operational risk. Among these four risks, production risk was the most dominant factor, as indicated by the high chicken mortality rate and inconsistent growth. These findings contribute to the development of Sharia-based risk management studies while broadening understanding of risk management in the smallholder livestock sector. This study concludes that systematic risk management integrated with the perspective of Sharia business management is important for supporting business sustainability, so business actors need to improve production management, financial recordkeeping, and operational efficiency. The implications of this study include theoretical contributions to the development of the Sharia risk management literature and practical contributions for business actors and policymakers in the agribusiness sector, while also opening opportunities for further research on the development of more comprehensive Sharia-based risk management models.